Pendekatan Pekerjaan Sosial Individu Untuk Meningkatkan Percaya Diri Remaja Di Panti Asuhan Ora Et Labora Medan - Ginting, Esekiel Pranata; Ritonga, Fajar Utama; Pirandi, Gusti (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
A is a teenager living in Ora Et Labora Orphanage, Medan, who struggles with math and self-confidence. This case work used a self-efficacy approach to support his learning motivation and self-belief. The intervention included simple activities like math practice, drawing, and light discussions. As a result, A became more confident and gradually improved. The process ended positively, with hopes for continued growth.